Pengaruh Pengunaan Media Labirin Terhadap Minat Belajar Peserta Didik Pada Muatan Materi PPKn Kelas III SDN 2 Seteluk - Alfandi Alfandi; I Nyoman Karma; Ilham Syahrul Jiwandono (Journal of Science Instruction and Technology, 2021)
This study aims to determine the effect of using labyrinth media on students' interest in learning the content of PPKn Class III SDN 2 Seteluk material. This type of research is experimental research, the research design is Quasi-Experimental Design in the form of a Nonequivalent Control Group Design. The subjects in this study were all third-grade students at SDN 2 Seteluk. Taking the subject through the technique of Census/Total Sampling. Data collection methods are questionnaires and observations. Questionnaires were used to obtain data in the form of students' interest in learning Civics, while observations were used to obtain data on the implementation of learning using labyrinth media. Based on the results of the Independent Sample T-Test test, the average difference in the posttest pretest of the experimental and control groups, and the effect size test, obtained a significant value or Sig(2-tailed) 0.012 which means it is smaller than 0.05, the value of the average difference the experimental group average was 1.7 while the control group was 0.5 and the effect size value was 0.787. This shows that Ho is rejected and Ha is accepted, so it can be concluded that the magnitude of the influence of the use of labyrinth media on students' learning interest in the content of PKKn class III SDN 2 Seteluk.